Penguatan Ekonomi KWT Srikandi Melalui Optimalisasi Digital Marketing Dan Diversifikasi Produk Olahan Cabai di Pringsewu - Khusnatul Amaliah; Dani Rofianto; Tiara Kurnia Khoerunnisa; Melisa Fitri; Kafka Armelsya; Ni Wayan Sevilla Sekarsari (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: This community service activity aims to strengthen the economy of the Srikandi Women Farmers Group (KWT) in Pekon Srikaton, Adiluwih District, Pringsewu Regency, through the implementation of digital marketing and diversification of processed chili products. The main problems of KWT include limited skills in chili processing and low utilization of digital technology for marketing. The method used is Participatory Action Research (PAR), with stages of socialization, chili processing training, digital marketing training, mentoring, and evaluation. The training activities increased the skills of KWT members in processing chili peppers into various products such as chili flakes, chili powder, and chili oil, as well as improving their ability to utilize social media for promotion. The results of the evaluation showed a significant increase in technical skills, entrepreneurial interest, and motivation of members to develop a business based on chili derivative products. This activity has proven to be effective in encouraging the economic independence of women through the use of technology and product innovation. Keywords: chili; digital marketing; product diversification Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat ekonomi Kelompok Wanita Tani (KWT) Srikandi di Pekon Srikaton, Kecamatan Adiluwih, Kabupaten Pringsewu, melalui penerapan digital marketing dan diversifikasi produk olahan cabai. Permasalahan utama mitra meliputi keterbatasan keterampilan dalam pengolahan cabai serta rendahnya pemanfaatan teknologi digital untuk pemasaran. Metode yang digunakan adalah Participatory Action Research (PAR), dengan tahapan sosialisasi, pelatihan pengolahan turunan cabai, pelatihan digital marketing, pendampingan, serta evaluasi. Kegiatan pelatihan menghasilkan peningkatan keterampilan anggota KWT dalam mengolah cabai menjadi berbagai produk seperti bon cabai, cabai bubuk, dan chili oil, serta meningkatkan kemampuan dalam memanfaatkan media sosial untuk promosi. Hasil evaluasi menunjukkan adanya peningkatan signifikan dalam kemampuan teknis sebesar 60%, minat berwirausaha, dan motivasi anggota untuk mengembangkan usaha berbasis produk turunan cabai sebesar 20%. Kegiatan ini terbukti efektif dalam mendorong kemandirian ekonomi perempuan melalui pemanfaatan teknologi dan inovasi produk. Kata kunci: cabai; digital marketing; diversifikasi produk